The Effect of Completeness of Filling Out Important Reports on Delay in Return of Medical Record Files - Mochammad Malik Ibrahim (EDUPEDIA Publisher, 2023)
Objective: The purpose of this study was to analyze the effect of the completeness of filling out important reports on several forms on the occurrence of delays in returning inpatient medical record files at the hospital. Methods: This type of research is quantitative analytic cross-sectional design. The population numbered around 643 with a total sample of 161 inpatient medical record files. Sampling technique with quota sampling. The primary data collection method was observation using a checklist sheet and data analysis using SPSS 24 for univariate analysis with frequency distribution, bivariate using the chi-square test and multivariate using logistic regression using the forward LR method. Results: The completeness of filling in important reporting on all forms studied has not reached 100% and the return of patient medical record files is still a lot of medical record files whose returns are late by 55.9% and the factors that have been proven to be factors that influence the occurrence of delays in returning medical record files are forms incomplete initial nursing assessment (p=0.034 and OR=9.438), incomplete filling of patient education forms (p=0.039 and OR=3.078). Conclusion: Factors that are proven to have an effect on the occurrence of delays in returning medical record files are incomplete filling of initial nursing assessment forms and incomplete patient education forms.